Spotlight environmental sustainability: a strategic priority for NICE. (18th August 2022) - Sharma, Manuj; Walpole, Sarah; Shah, Koonal
Abstract: This article provides the context for the ambition outlined in the the National Institute for Health and Care Excellence (NICE) 2021–2026 strategy to 'lead globally on the potential to include environmental impact data in its guidance to reduce the carbon footprint of health and care'. Anthropogenic environmental changes pose a catastrophic risk to human health, with potential to widen national and global health inequalities. Recognising the fact that NICE guidance influences the way health and care is delivered and its consequent environmental impact, NICE has included environmental sustainability among its strategic priorities. This article outlines the work underway to meet this sustainability agenda at NICE.